The role of insulin-like growth factor I-II receptor on development of pleomorphic adenoma - Arslan, Ibrahim; Keles, Erol; Ozercan, I. Hanifi; Tokdemir, Mehmet; Karlidag, Turgut; Kaygusuz, Irfan; Yalcin, Sinasi (Springer, 2017)
Pleomorphic adenoma is a slow-growing salivary gland tumor frequently arising from the parotid gland. In this study, we investigated the role of the insulin-like growth factor I-II receptor (IGFI-IIR) levels on the development of parotid gland pleomorphic adenomas. The study included 20 males and 20 females who had superficial parotidectomy with a histopathological diagnosis of pleomorphic adenoma in FA +/- rat University Otorhinolaryngology Clinic between 2000 and 2011. The ages of the patients ranged between 20 and 50 years. The control tissues were obtained unilaterally from the parotid glands of five female and five male cadavers during autopsy, and consisted of 0.5 x 0.5 cm sized normal parotid gland tissues. The expression of IGFI-IIR were measured in both tumor and tumor-free normal parotid tissue in the study group while only the normal parotid tissues were studied in the cadavers. Primary polyclonal antibodies against IGFI-IIR were used with Streptavidin-Biotin Complex method for immunohistochemical staining of both the study and the control groups' tissue sections. In this study, the IGFI-IIR levels were found significantly higher in the pleomorphic adenoma tissue (p < 0.05). In addition, IGFI-IIR expression was greater in normal parotid tissues of the study group when compared to the normal parotid tissues of the cadavers. However, the difference was not statistically significant (p > 0.017). Greater expression for IGFI-IIR in pleomorphic adenoma when compared to normal parotid tissues of the patients and the cadavers suggests that IGFI-II may be important factors in the development of pleomorphic adenoma.
Keywords: Pleomorphic adenoma; IGF I-IIR